Analisis Lukisan Berjudul Blekok Cafe dalam Upaya Mengupas Rahasia Karya Eko Alif Vernanda - Setyawan, Haris; Anggriani, Swastika Dhesti (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2025)
The painting "Blekok Cafe" by Eko Alif, created in 2024, was chosen as the research object to explore the messages and values ​​in the artwork. The researcher felt complex emotions in this painting, in the form of a contradiction between luxury and anger in the figure of the Blekok bird that appears alienated from its natural habitat. This study aims to identify and analyze the values ​​and synthesis contained in the work, especially in the context of the relationship between humans, nature, and other living things. The method used is descriptive qualitative with a holistic critical approach. Data collection was carried out through interviews with the artist, observation of the artwork, and analysis of documents related to the social and environmental context. Data were collected from three main sources: genetic information (from the artist), objective information (from the artwork), and affective information (from devotees). A triangulation of methods was used to validate the findings obtained. The results of the study show that this painting depicts Eko Alif's anxiety about the negative impact of human activities on nature, especially on the disturbed habitat of the blekok bird. The social value contained in this painting is the importance of reminding each other to maintain harmony between humans, nature, and other living things. The painting "Blekok Cafe" conveys a strong message about the need for awareness of the existence of nature and other living things that are often overlooked in the materialistic human world.